The psychopathologies of cognitive capitalism : Part Three - Neidich, Warren (Berlin : Archive Books, 2014)
Essays by Meena Alexander ; Amanda Beech ; Franco 'Bifo' Berardi ; Ray Brassier ; David Burrows ; Tyler Coburn ; Jacquelene Drinkall ; Mark Fisher ; Bronac Ferran ; Matthew Fuller ; Liam Gillick ; Melanie Gilligan ; Scott Lash and Anthony Fung ; Lambros Malafouris ; Anna Munster ; Warren Neidich ; Dimitris Papadopoulos ; Luciana Parisi ; John L; Protevi ; Howard Slater ; Kerstin Stakemeier ; Ryan Trecartin ; Marina Vishmidt
Published on the occasion of "The Psychopathologies of Cognitive Capitalism: Part Three at Goldsmits, University of London in May 2014.
boek
Keywords: Neidich, Warren